The Effect of Organizational Citizenship Behavior (OCB) and Commitment on Employee Performance Through Job Satisfaction as a Mediating Variable in Indonesian SMEs - Pahlevi, Akbar; Nirmala, Nirmala (IJOSMAS, 2023)
The aim of this research is to analyze the relationship between organizational citizenship behavior (OCB) variables and employee performance, analyze the relationship between employee commitment variables and employee performance, analyze the relationship between organizational citizenship behavior (OCB) variables and job satisfaction, analyze the relationship between employee commitment variables and job satisfaction, analyze the relationship between job satisfaction variables and employee performance. This research method is quantitative through an online survey, research data was obtained by distributing online questionnaires to 435 SMEs owners in Indonesia who were selected using a simple random sampling method. Data analysis used structural equation modeling (SEM) partial least squares (PLS) with the SmartPLS 3.0 software tool. The questionnaire contains statement items and is designed using a 9-point Likert scale. The stages of data analysis are validity testing, reliability testing and direct and indirect hypothesis testing or mediation effect testing. The independent variables in this research are organizational citizenship behavior (OCB) and employee commitment , the dependent variable is employee performance and the mediating variable is the job satisfaction variable. The results of the research show that the organizational citizenship behavior (OCB) variable has a positive and significant relationship to employee performance, the employee commitment variable has a positive and significant relationship to employee performance, the organizational citizenship behavior (OCB) variable has a positive and significant relationship to job satisfaction, employee variables. commitment has a positive and significant relationship with Job Satisfaction, the job satisfaction variable has a positive and significant relationship with employee performance. The novelty of this research is the creation of a relationship model for the variables organizational citizenship behavior, employee commitment, employee performance and the mediating role of job satisfaction variables.